Understanding depression in basic education teachers: evidence from Brazil - Santos, Karen Christina Rodrigues dos; Machado, Arthur V.; Rocha, Sarah; Martins, Rony Magalhães; Nudelman, Marta; Pereira, Mirtes Garcia; de Oliveira, Letícia; Staniscuaski, Fernanda (Frontiers in Education, 2026)
IntroductionTeacher mental health is a growing global concern, particularly in under-resourced educational systems. Depression among educators compromises not only individual well-being but also the quality and equity of education. This study investigates the prevalence of depressive symptoms among Brazilian basic education teachers and explores how structural inequalities, particularly gender, race, parenthood, and prior psychiatric history, contribute to mental health outcomes.MethodsA total of 273 teachers from public and private schools across Brazil responded to an online survey including sociodemographic items and the Patient Health Questionnaire 9 (PHQ 9). Statistical analyses included Mann–Whitney tests and multiple logistic regression to compare group differences and estimate predictors of probable depression.ResultsNearly half of participants (49.5%) scored above the PHQ-9 cutoff for probable depression. Female teachers and those with a history of psychiatric diagnosis were significantly more likely to report depressive symptoms. Black teachers exhibited higher scores and greater proportions above the cutoff. Parenthood showed no significant association with depression in this sample.DiscussionThese findings reveal that the mental health burden among teachers in Brazil is alarmingly high and closely tied to broader structural conditions. The combination of chronic emotional demands, institutional precarity, and intersecting social inequalities places educators, especially women and Black professionals, at heightened risk. These results emphasize the need for systemic policy responses that move beyond individual resilience frameworks and instead address the organizational, social, and racialized dynamics that shape teacher well-being.ConclusionThis study contributes to the international dialogue on teacher mental health. The findings underscore the urgency of implementing structural interventions and equity-oriented policies that protect educators from cumulative psychological strain. Addressing teacher mental health is not only a matter of individual care but a strategic imperative for the sustainability and inclusivity of education systems worldwide.